THE IMPLEMENTATION OF ELECTRONIC RECORDS MANAGEMENT SYSTEM (ERMS) IN PUBLIC SECTOR - Wan Hashim, Wan Nor Syazana; Ahmad, Siti Nurul Akma; Eshak, Erratul Shela (Jurnal ’Ulwan, 2022)
Challenges in the management of electronic records (e-records) have led to the adoption of Electronic Records Management System (ERMS) to enhance their management. The spread of technology use has led to the creation of different types of records and ERMS can provide an integrated way to manage these different types of records effectively. Most government agencies around the world have adopted the use of ERMS to improve the management of e-records. However, many initiatives to implement ERMS especially in developing countries have failed. Therefore, this study was conducted to identify the hindrance factors for the implementation of ERMS particularly in government sectors. This review paper gathered the data from the previous literatures which discussed on the issues and challenges in the ERMS implementation and other related topics. Based on the reviews, the factors that have been cited as major hindrances include lack of top management support and resistance to change by users of the system. This study will benefit to the records manager and organization as the recommendations and a best-practice for managing electronic records in support of ERMS in government sector have been provided.